2016
DOI: 10.1007/s11882-016-0634-5
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil ETosis and DNA Traps: a New Look at Eosinophilic Inflammation

Abstract: The traditional paradigm of eosinophils as end-stage damaging cells has mainly relied on their release of cytotoxic proteins. Cytokine-induced cell survival and secretion of granular contents from tissue-dwelling eosinophil are thought to be important mechanisms for eosinophilic inflammatory disorders, although the occurrence of cytolysis and its products (i.e., free extracellular granules) has been observed in affected lesions. Recent evidence indicates that activated eosinophils can exhibit a non-apoptotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 85 publications
1
71
0
6
Order By: Relevance
“…43,44 Upon entry into circulation, eosinophils have a short half-life before distribution into diverse tissue sites, including the lung. 43,44 Upon entry into circulation, eosinophils have a short half-life before distribution into diverse tissue sites, including the lung.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Upon entry into circulation, eosinophils have a short half-life before distribution into diverse tissue sites, including the lung. 43,44 Upon entry into circulation, eosinophils have a short half-life before distribution into diverse tissue sites, including the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, we should note that SYTOX Green‐positivity could overestimate the amount of NETs because of the presence of a small population of SYTOX Green‐positive MPO‐negative cells. Since it has been demonstrated that eosinophils can release their chromatin fibers akin to neutrophils 23, the SYTOX Green‐positive MPO‐negative population could be composed of eosinophils with extracellular chromatin fibers. Henceforth, cells which are doubly positive for SYTOX Green and MPO should be regarded as neutrophils that formed NETs.…”
Section: Discussionmentioning
confidence: 99%
“…This proresolving effect is presumably caused by an IL-13-dependent shift of macrophages toward an antiinflammatory phenotype characterized by a high expression of arginase 1 and/or by the production of antiinflammatory lipids such as protectin D1 (15). Although not to the same extent as neutrophils, eosinophils also possess considerable protease activity that might exert immunoregulatory effects similar to neutrophils (22,23). However, eosinophil granules often stay intact during extracellular trap formation (22), which may possibly affect cytokine degradation.…”
Section: Role Of Eosinophils In Degradation Of Cytokines/chemokines Amentioning
confidence: 99%